Implementation of COVID-19 Protocols and Tele-Triage in an Academic Ophthalmology Department - Scanzera, Angelica C.; Cole, Emily; Valikodath, Nita; Pham, Chau; Vajaranant, Thasarat Sutabutr; Edward, Deepak P.; Hallak, Joelle A.; Leiderman, Yannek I.; Kalinoski, Lauren; MacIntosh, Peter; Aref, Ahmad A.; Shukla, Deepak; Bhat, Pooja; Tu, Elmer; Chan, R.V. Paul (Journal of Academic Ophthalmology, 2020)
Background The coronavirus disease-2019 (COVID-19) pandemic has affected academic ophthalmology departments globally, causing changes in educational, research, and clinical operations in the short and long term. Healthcare workers are at higher risk of contracting the disease and given early reports suggestive of transmission through the tear film in COVID-19 cases with conjunctivitis, and close proximity during examination, eye care providers in particular may be at increased risk.Objective To provide the experience from a single academic ophthalmology program in responding to the COVID-19 pandemic.Methods This article describes the changes executed in the Department of Ophthalmology and Visual Sciences at the University of Illinois at Chicago, Illinois Eye and Ear Infirmary, with emphasis on the implementation of a tele-triage process for urgent visits.Results In response to the pandemic, our department made rapid changes to its departmental protocols for education, research, and patient management. Early measures focused on limiting face-to-face interactions among patients, staff, residents, and faculty, decreasing the risk of exposure to disease while also providing access for patients in urgent need of care.Conclusion We hope that the UIC experience will assist other academic tertiary referral centers in maximizing their opportunities to deliver excellent patient care while minimizing risks to patient and provider, all while continuing to provide a quality graduate medical educational experience during and beyond the pandemic.
Keywords: coronavirus; SARS-CoV-2; tele-triage; telehealth; resident education; medical education